Mengembangkan Kecerdasan Spiritual Mahasiswa di Perguruan Tinggi - Tampubolon, Simon M. (Humaniora, 2013)
The article discusses about how to develop spiritual intelligence of students in the college environment. This article describes pinciples of the application of the six ways of spiritual intelligence development into learning models, assignments, and campus life. The principles should be done by considering the meaning of the spiritual, developmental characteristics of students, and the characteristics of students’ spiritual development.